2020
DOI: 10.1186/s13041-020-00629-x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor protein tyrosine phosphatase delta is not essential for synapse maintenance or transmission at hippocampal synapses

Abstract: Members of the leukocyte common antigen-related receptor protein tyrosine phosphatase (LAR-RPTP) family, comprising PTPσ, PTPδ and LAR, are key hubs for presynaptic assembly and differentiation in vertebrate neurons. However, roles of individual LAR-RPTP members have not been investigated using member-specific conditional knockout mice. Here, we show that loss of PTPδ had no overt effect on synapse development in mouse cultured hippocampal neurons. Moreover, loss of PTPδ in presynaptic CA1 hippocampal neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…To support this, mutations in PTPσ and PTPδ genes are associated with ASD and/or attention-deficit hyperactivity disorder (ADHD; Takahashi and Craig, 2013 ). Conversely, however, a more recent study has shown that PTPδ conditional KO does not affect release probability (Han et al, 2020b ). Moreover, recent studies on conditional KO of all LAR-RPTPs have shown that they are involved in NMDAR-mediated synaptic transmission and LTP without affecting AMPAR-mediated transmission or synapse number (Sclip and Südhof, 2020 ).…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 96%
“…To support this, mutations in PTPσ and PTPδ genes are associated with ASD and/or attention-deficit hyperactivity disorder (ADHD; Takahashi and Craig, 2013 ). Conversely, however, a more recent study has shown that PTPδ conditional KO does not affect release probability (Han et al, 2020b ). Moreover, recent studies on conditional KO of all LAR-RPTPs have shown that they are involved in NMDAR-mediated synaptic transmission and LTP without affecting AMPAR-mediated transmission or synapse number (Sclip and Südhof, 2020 ).…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 96%
“…Recent literature has provided apparently conflicting observations regarding the role of LAR-RPTPs in synapse formation, probably due to the differential experimental approaches that have been carried out. While RNAi-mediated knockdowns of LAR-RPTPs in cell cultures have shown deficiencies in synaptic formation and neurotransmitter release ( Dunah et al, 2005 ; Ko et al, 2015 ; Han et al, 2018 ), recent studies using conditional knockout animals have suggested that PTPRD and PTPRS are not essential for synaptic formation at least in the hippocampus ( Han et al, 2020c ; Sclip and Südhof, 2020 ). Despite the clear difference between both experimental models, it is important to highlight that other studies using LAR-RPTP knockout mice have shown impairments in behaviors such as spatial learning, memory, motor control and non-REM sleep as discussed later ( Wallace et al, 1999 ; Uetani et al, 2000 ; Meathrel et al, 2002 ; Kolkman et al, 2004 ; Park et al, 2020 ).…”
Section: Lar-rptps In Synaptic Formation and Functionmentioning
confidence: 99%
“…Thus, live-cell imaging analyses could be employed to precisely determine the dynamics of synaptic vesicle material influx and efflux in presynaptic structures. High-resolution electron microscopic analyses are sometimes warranted to further investigate possible anatomical defects that cannot be discerned by light microscopy, as we have done in our recent studies ( Han et al., 2020a ; Han et al., 2020b ).…”
Section: Limitationsmentioning
confidence: 92%
“…Cultured neurons can be infected with recombinant lentiviruses expressing the gene of interest. In our recent studies ( Han et al., 2020a ; Han et al., 2020b ), we produced lentiviruses expressing Cre recombinase (using inactive Cre recombinase as a negative control) and used them to infect cultured (∼DIV3–4) neurons derived from mice harboring a floxed allele of the targeted presynaptic adhesion molecules. Lentiviruses are produced in HEK293T cells by transfections of the lentivirus backbone vectors, psPAX2 and pMD2.G, followed 72 h later by replacement of the supernatant with neuron culture media (i.e., complete neurobasal media).…”
Section: Expected Outcomesmentioning
confidence: 99%